A rare case presentation of an anomalous uterus mimicking ovarian tumour - M., Mohanambal; sheelaa, Wills G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Mullerian anomalies occur in 1:1000-3000 females. Uterus didelphys and obstructed hemangioma with a septum contribute to 10% anomalies. Young girls present with severe dysmenorrhea, hematometra, hematocolpos and recurrent pregnancy loss. A 16-year-old teenager presented like a torsion of complex ovarian tumour is presented here. Intra operative findings was uterus didelphys with well-developed 2 horns, tubes and ovaries. On left ovary, a hemorrhagic corpus luteal cyst of size 5.2*4cm was seen with 50ml of hemoperitoneum. Diagnosis was confirmed histopathologically. This case is reported for the unusual presentation of an anomalous uterus mimicking torsion ovarian tumour.